2011
DOI: 10.1111/j.1365-2036.2011.04783.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: the pathophysiology and management of polycystic liver disease

Abstract: SUMMARY BackgroundPolycystic liver diseases (PCLD) represent a group of genetic disorders in which cysts occur solely in the liver, or together with renal cysts. Most of the patients with PCLD are asymptomatic, however, in some patients, expansion of liver cysts causes invalidating abdominal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
92
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 102 publications
(309 reference statements)
1
92
0
Order By: Relevance
“…It reflects disease severity and is useful when choosing treatment options. Recently, several reports on PLD treatment have recommended aspiration sclerotherapy, cyst fenestration, and liver resection for Gigot type 1 or 2 PLD and liver transplantation for type 3 PLD; however, no standardized criteria for the selection of treatment exist [5,23,35,46,59,64,65,[73][74][75] . In our series, all patients had Gigot type 2 PLD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It reflects disease severity and is useful when choosing treatment options. Recently, several reports on PLD treatment have recommended aspiration sclerotherapy, cyst fenestration, and liver resection for Gigot type 1 or 2 PLD and liver transplantation for type 3 PLD; however, no standardized criteria for the selection of treatment exist [5,23,35,46,59,64,65,[73][74][75] . In our series, all patients had Gigot type 2 PLD.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was difficult to control complications caused by small hepatic cysts in PLD. The goals of treatment for PLD are to alleviate abdominal symptoms and prevent their recurrence by decreasing liver volume [5] . Symptom recurrence is caused by the growth of new cysts or the re growth of treated cysts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we recently demonstrated that a reduction of ≥120mL in liver volume after 6 months has a high positive predictive value of improving complaints, a reduction which lies above the 95% upper limit of the confidence intervals of the differences in LV assessed by two software methods measuring the same LV [11]. Also mTOR inhibitors might reduce liver volume, although the data are less robust and combination of octreotide and everolimus did not increase the LV reducing effect of octreotide alone [3,12].…”
Section: Introductionmentioning
confidence: 99%
“…The natural history of PCLD, regardless of the genetic mutation, is similar [1][2][3]. Most of the patients with PCLD stay asymptomatic, but 2-5% of patients will develop symptomatic hepatomegaly as a result of the continuous increase in volume and number of liver cysts.…”
Section: Introductionmentioning
confidence: 99%